Penerapan Marketing Management Dengan Metode Digital Marketing Untuk Meningkatkan Penjualan Home Industry: (Studi Kasus Agung Dimsum Medan Tembung) - Maulana Ma’ruf (Jurnal Publikasi Ilmu Manajemen, 2023)
Application of Marketing Management with Digital Marketing Method to Increase Home Industry Sales. Increasing sales is a crucial factor for the sustainability of Home Industry businesses. In the current digital era, the application of Digital Marketing methods has become an effective strategy to achieve this goal. This research aims to identify and analyze the implementation of marketing management using the Digital Marketing method to increase sales in the context of the Home Industry. This study uses a qualitative approach with in-depth interviews and direct observations as data collection methods. The research sample consists of Home Industry owners who have implemented Digital Marketing in their marketing strategy, such as Agung Dimsum. The collected data is then analyzed using qualitative analysis techniques such as thematic coding and data triangulation. The research results show that the application of marketing management with the Digital Marketing method has a positive impact on Home Industry sales. In this context, digital marketing involves the use of various online platforms such as social media, websites, and email marketing to promote products and reach a broader target market. This research also identifies several supporting factors that contribute to the success of marketing management with the Digital Marketing method. These factors include a good understanding of consumers and the market, engaging and relevant content, the use of search engine optimization techniques, and active interaction with customers through social media. Thus, the application of marketing management with the Digital Marketing method can be an effective strategy for Home Industry in increasing sales. These findings provide valuable insights for Home Industry owners who want to harness the potential of digital marketing to achieve business success.